MAKKATTE AND THE INVERSION OF AUTHORITY: Symbolic Negotiation of Living Hadith in Palopo, Indonesia - Abbas Langaji; M. Ilham; Muhammad Irfan Hasanuddin (PAPPASANG, 2026)
This article examines the symbolic negotiation of makkatte (female circumcision) among Bugis Muslims in Palopo, South Sulawesi, within the global discourse on FGM/C. Despite international health frameworks and national regulations that classify FGM/C as a violation of bodily integrity, the practice in Palopo has transformed from an invasive procedure into a non-invasive symbolic ritual. Drawing on ethnographic research, including in-depth interviews and participant observation, this study employs symbolic anthropology and the Living Hadith framework. The findings reveal that makkatte persists as a form of “demedicalized symbolization,” bridging modern medical ethics and socio-religious needs for identity marking. A weakly authenticated hadith gains “sociological validity” through collective practice, while women’s agency—particularly that of mothers and grandmothers—plays a central role in sustaining the ritual as negotiated piety. This study highlights how Muslim communities reinterpret religious texts to navigate global modernity and local sacred traditions.